Indicators of physiological maturity of sibipiruna (Poincianella pluviosa (dc.) L.p.queiroz) seeds (Research, Society and Development, 2021)
The recovery of degraded areas has demanded studies that enable the development of native species implanted in the recovery process of these areas. Therefore, during the production of seedlings, an important parameter to be understood is the physiological maturity, the moment when the transfer of dry mass from the plant to the seeds ceases. With this, the present work aimed to determine the best stage for the harvest of the sibipiruna fruits, based on the physiological maturity indicators, aiming at obtaining quality seeds. Were collected the fruits (pods) from five matrices located in Paragominas-PA. Evaluated the size, water content, dry weight, germination and germination speed index for three treatments based on the color of the fruits, namely: stage I - totally green fruits; stage II - green-opaque fruits; and stage III - totally dark brown fruits. The study was conducted in a completely randomized design, with tests of normality, homogeneity of data and comparison of means with significance of 5%. There was no significant difference between treatments for water content and dry weight. Seeds in stage III (higher maturity) showed smaller sizes, higher germination and emergence speed. Stage III showed better results and can be considered as the most appropriate for the collection of fruits aiming at greater germination and vigor.